A Mini-Review: Metabolites of Kappaphycus alvarezii - Mangkurat, Bayu (Science Technology and Management Journal, 2024)
The aim of this paper is to highlight physiology approach in in the context of seaweed studies, especially Kappaphycus alvarezii. First, introduction about seaweed are reviews. Second, physiology and metabolites studies in seaweed, especially primary metabolites, and secondary metabolites in K. alvarezii are presented and discussed. As conclusion, metabolites studies may provide key sources of information that can be tools to assess the application of biotechnological-based approaches for conservation, industry, and management. .